Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Pada Usahatani Bawang Merah Di Kabupaten Gorontalo - Mohammad Zubair Hippy (Jurnal AGRIBIS, 2024)
This research aims to analyze farmers' income in shallot farming and examine the factors that determine farmers' income in shallot farming in Gorontalo Regency. The approach used in this research is quantitative, employing descriptive and correlational methods. A total sample of 52 respondents was obtained using Krejcie and Morgan's sample size calculation. Data collection methods include questionnaires, interviews, and documentation. Data analysis involves income analysis and multiple linear regression. The results of the study found that (1) the average income value of farmers in shallot farming in Gorontalo Regency is 27.759%, with a profit margin value of 42.688% when prices are high and a profit margin of only 12.829% when prices are standard. The income of shallot farmers is quite vulnerable to price declines, so price stability needs to be pursued by various relevant stakeholders. (2) Land per planting season, capital per planting season, and labour per planting season together have a significant effect on farmers' income in shallot farming in Gorontalo Regency, with a coefficient of determination of 88.10%. Partially, it was found that the land area per planting season had a positive but insignificant effect on farmers' income in shallot farming, with an influence of 8.50%. Capital per planting season has a positive and significant effect on farmers' income in shallot farming, with an influence of 68.70%, and labour per planting season has a positive and significant influence on farmers' income in shallot farming, with an influence of 10.90%. Keywords: Income; Land; Capital; Labour; Shallots